The Model for Calculation the Hall Effect Parameter - Kleiza, J.; Kleiza, V. (Nonlinear Analysis: Modelling and Control, 2004)
A method for calculating the values of specific resistivity ρ as well as the product µHB of the Hall mobility and magnetic induction on a conductive sample of an arbitrary geometric configuration with two arbitrary fitted current electrodes of nonzero length and has been proposed an grounded. During the experiment, under the constant value U of voltage and in the absence of the magnetic field effect (B = 0) on the sample, the current intensities I(0), IE(0) are measured as well as the mentioned parameters under the effect of magnetic fields B1, B2 (B1 ≠ B2), i.e.: IE(β(i)), I(β(i)), i = 1, 2. It has been proved that under the constant difference of potentials U and sample thickness d, the parameters I(0), IE(0) and IE(β(i)), I(β(i)), i = 1, 2 uniquely determines the values of the product µHB and specific resistivity ρ of the sample. Basing on the conformal mapping method and Hall’s tensor properties, a relation (a system of nonlinear equations) between the above mentioned quantities has been found.
Keywords: mathematical modelling; conductivity; Hall effect